Genetic Recombination Between Stromal and Cancer Cells Results in Highly Malignant Cells Identified by Color‐Coded Imaging in a Mouse Lymphoma Model. Issue 12 (9th June 2017) - Nakamura, Miki; Suetsugu, Atsushi; Hasegawa, Kousuke; Matsumoto, Takuro; Aoki, Hitomi; Kunisada, Takahiro; Shimizu, Masahito; Saji, Shigetoyo; Moriwaki, Hisataka; Hoffman, Robert M.
ABSTRACT: The tumor microenvironment (TME) promotes tumor growth and metastasis. We previously established the color‐coded EL4 lymphoma TME model with red fluorescent protein (RFP) expressing EL4 implanted in transgenic C57BL/6 green fluorescent protein (GFP) mice. Color‐coded imaging of the lymphoma TME suggested an important role of stromal cells in lymphoma progression and metastasis. In the present study, we used color‐coded imaging of RFP‐lymphoma cells and GFP stromal cells to identify yellow‐fluorescent genetically recombinant cells appearing only during metastasis. The EL4‐RFP lymphoma cells were injected subcutaneously in C57BL/6‐GFP transgenic mice and formed subcutaneous tumors 14 days after cell transplantation. The subcutaneous tumors were harvested and transplanted to the abdominal cavity of nude mice. Metastases to the liver, perigastric lymph node, ascites, bone marrow, and primary tumor were imaged. In addition to EL4‐RFP cells and GFP‐host cells, genetically recombinant yellow‐fluorescent cells, were observed only in the ascites and bone marrow. These results indicate genetic exchange between the stromal and cancer cells. Possible mechanisms of genetic exchange are discussed as well as its ramifications for metastasis. J. Cell. Biochem. 118: 4216–4221, 2017. © 2017 Wiley Periodicals, Inc. Abstract : This manuscript demonstrates genetic recombination between stromal and cancer cells by color‐coded imaging in a mouse lymphoma model.